Pengembangan Penuntun Praktikum Pada Materi Sel dan Pelintasan Zat Melalui Membran Kelas XI SMA/MA dengan Pendekatan Inkuiri Bebas Dimodifikasi - Nurhadi, Nurhadi; Zural, Mimin Mardhiah; Oktafially, Dora (Bioscientist : Jurnal Ilmiah Biologi, 2024)
During the 11th-grade biology practicum at SMA/MA, students use biology textbooks from the library and worksheets written by the teacher on sheets of paper as guides for their exercises. However, the availability of biology books in the library is insufficient, and not all students can access them. This research aims to develop a practicum guide on human mobility material for 11th-grade SMA/MA students using a modified free inquiry approach. This development research uses the Plomp model, which consists of three development phases: the preliminary research phase, the prototyping phase, and the assessment phase. The research instruments used to obtain data on validity, feasibility, ease of use, and effectiveness were questionnaires with a Likert scale. The effectiveness of students' attitudes was assessed with attitude observation sheets, and the effectiveness of skills was evaluated with practicum report assessments. The research data were analyzed using percentage formulas and descriptively analyzed to obtain results that fit the categories of validation, feasibility, ease of use, and effectiveness. The results of this research are: (1) the practicum guide was deemed very valid (85.31%) based on expert validation results; (2) the practicum guide was deemed very feasible (88.33%) based on one-to-one assessment results and very feasible (86.67%) based on small group assessment results; (3) the practicum guide was considered very easy to use (93.13%) based on teacher evaluations and very easy to use (86.31%) based on student evaluations; (4) the practicum guide was very effective for attitude aspects (96.87%) and skill aspects (81.52%).